Spirituality, Art, and Memory in Installations by John Hitchcock and Eric-Paul Riege - Stolte, Sarah Anne (Religion and the arts, 2025)
The installation artworks of John Hitchcock and Eric-Paul Riege exemplify the intersection of art, memory, and spirituality in contemporary Indigenous arts, functioning as acts of resilience and survival. Riege’s immersive installations, which incorporate traditional Diné weaving and performance, transform galleries into spaces of ancestral memory and spiritual reflection while critiquing historical representations of Indigenous identities. Similarly, Hitchcock’s multi-media installations use traditional Comanche symbols alongside contemporary elements to explore themes of historical trauma and cultural resilience. Together, their work underscores the vital role of art in preserving and reinterpreting Indigenous identities, challenging static perceptions, and emphasizing the dynamic nature of contemporary Indigenous art.